TI_GERICHTE 52.2013.307 vom 7. Oktober 2014 , Licenza edilizia. Depositi e manufatti fuori della zona edificabile - TI Tribunale d'appello (2014)
Licenza edilizia. Depositi e manufatti fuori della zona edificabile